2021
DOI: 10.1021/jacs.0c12845
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Evidence for Aromatic Stabilization Energy in Large Macrocycles

Abstract: Enhanced thermodynamic stability is a fundamental characteristic of aromatic molecules, yet most previous studies of aromatic stabilization energy (ASE) have been limited to small rings with up to 18 π-electrons. Here we demonstrate that ASE can be detected experimentally in π-conjugated porphyrin nanorings with Hückel circuits of 76-108 π-electrons. This conclusion is supported by analyzing redox potentials to calculate the energy change for isodesmic reactions that convert an aromatic ring to an antiaromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 65 publications
(113 reference statements)
4
44
0
Order By: Relevance
“…Hence, if the corresponding experimental values are only −1.87 ppm and −2.83 ppm, respectively, this is clearly suggesting that c‐P6⋅T6 6+ is either very weakly aromatic or non‐aromatic, as the CAM‐B3LYP results indicate. This result is further reinforced by a recent finding [57] that the experimental aromatic stabilization energy of c‐P6⋅T6 6+ is ca. 1.2 kcal mol −1 , which is relatively small for an aromatic molecule.…”
Section: Resultssupporting
confidence: 61%
“…Hence, if the corresponding experimental values are only −1.87 ppm and −2.83 ppm, respectively, this is clearly suggesting that c‐P6⋅T6 6+ is either very weakly aromatic or non‐aromatic, as the CAM‐B3LYP results indicate. This result is further reinforced by a recent finding [57] that the experimental aromatic stabilization energy of c‐P6⋅T6 6+ is ca. 1.2 kcal mol −1 , which is relatively small for an aromatic molecule.…”
Section: Resultssupporting
confidence: 61%
“…These results bring about two important conclusions.F irst of all, it reinforces the idea that CAM-B3LY P(or M06-2X) are more adequate methods to obtain the geometry of potential aromatic molecules than B3LYP,w hich incurs large delocalization errors.Second, through various aromaticity probes,we have shown that the B3LYP geometry of c-P6 6+ corresponds to aq uite aromatic molecule with d o' Àd o = À7.23 ppm, and Dd a = À12.26 ppm. Hence,ifthe corresponding experimental values are only À1.87 ppm and À2.83 ppm, respectively,this is clearly suggesting that c-P6•T6 6+ is either very weakly aromatic or non-aromatic,a st he CAM-B3LYP results indicate.This result is further reinforced by arecent finding [57] that the experimental aromatic stabilization energy of c-P6•T6 6+ is ca. 1.2 kcal mol À1 ,w hich is relatively small for an aromatic molecule.…”
Section: Methodsmentioning
confidence: 70%
“…[5] Global (anti)aromaticity was also confirmed by magnetic susceptibility measurements, [2] and by analysis of oxidation potentials and rates of conformational exchange. [7] Global ring currents were not detected in the ground states of neutral nanorings, but variation in the fluorescence behavior of neutral c-PN[bN] cyclic oligomers as a function of ring size, N, indicate that the neutral singlet excited states exhibit global (anti)aromaticity. [4] In a recent Research Article, [9] Casademont-Reig, Guerrero-Avilés, Ramos-Cordoba, Torrent-Sucarrat, and Matito compared our experimental 1 H NMR chemical shifts for c-P6[b6] Q (Q = 0, +4, +6 and +12) with those that they calculated using two different functionals, B3LYP and CAM-B3LYP.…”
mentioning
confidence: 91%
“…Recently, we published experimental evidence for global aromaticity and antiaromaticity in porphyrinbased nanorings with Hückel circuits of up to 162 π-electrons. [2][3][4][5][6][7][8] These macrocycles are dramatically larger than previouslyreported aromatic rings, and we have suggested that studies on such large macrocycles could shed light on the similarity between aromatic ring currents and persistent currents in nonmolecular quantum rings. [8] They may also help elucidate a link between aromatic ring currents and the currents that flow through molecular wires driven by a voltage bias.…”
mentioning
confidence: 99%